Caddisflies (Trichoptera, Insecta) as bioindicator of water quality assessment in a small stream in Northern Thailand - Thamsenanupap P.,; Seetapan K,; Prommi T., (Penerbit Universiti Kebangsaan Malaysia, 2021)
The influence of environmental variables and the potential as bioindicators of larval stages of the species of Trichoptera were evaluated in a small stream in northern Thailand from January to November 2017. A total of 1,191 individual caddisfly larvae belonging to 7 families and 13 genus were found. The larvae of the family Glossosomatidae were the most abundant, followed by Hydropsychidae and Calamoceratidae. The genus Glossosoma, Hydromanicus and Hydropsyche were the most abundant genus in this study. Results of the CCA ordination showed that total dissolved solids, electrical conductivity, and water temperature were the most important factors affecting the abundance and diversity of caddisfly larvae. Changes in the caddisfly larvae may indicate changes in physicochemical factors owing to urbanization or other anthropogenic. The results showed that the order Trichoptera, identified to the species or genus level, can potentially be used to assess environmental water quality status in freshwater ecosystems. This study suggested that species richness of aquatic insects may indicate the conservation value of the habitats because of their significant responses to environmental factors.